THE SELF IN THE WORLD: OVERCOMING CLASSICAL DUALISM AND SHAPING NEW LANDMARKS - U. I. Lushch (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Based on tracing dualistic tendencies in the history of the concept “self” formation, the paper aims to clarify in what way dualism – contradistinction of the self and sociality, in particular – is being overcome in phenomenological and hermeneutic approaches to the self. Methodology. The systematic and integrative approaches, hermeneutic, phenomenological and retrospective methods, comparative analysis, description and synthesis underlie the research conducted in this paper. Theoretical basis. The development of the concept “self” is traced based on historical retrospective of its definitions. The paper shows the influence of Kantian interpretation of the self upon the contemporary approaches, presents the comparative analysis of the most recent definitions of the self and illustrates the study results on the relation of the self to the body, the world, the narration and the identity with reference to Martin Heidegger, Paul Ricoeur and Charles Taylor in particular. Originality. An integration of phenomenological and hermeneutic approaches to the self is introduced in the paper. It is argued that phenomenological and hermeneutic interpretations can be represented as complementing each other, since they share the anti-dualist perspective and interweave in description of the key aspects of the self, particularly sociality and language. Conclusion. Dualism is overcome in the contemporary interpretations of the self as it is clear from the phenomenological and hermeneutic approaches example. There is no more acute opposition between the self and the world, the self and the body, the self and the social life of a person. The self is considered as “being-in-the-world” which unfolds through intersection of different dimensions: subjectivity, body, temporality, language and sociality. Sociality provides the self with a moral framework through identity and enables conditions for person’s self-fulfillment, since the self reaches completeness only by transcending itself towards the others. The modern discovery of the self entails the need to invent a new type of solidarity.